A statistical quality control study on D. Y. Manufacturing Corporation - Capili, Robert Jerome D.; Galema, Nittanee Frances B.; Juan Maria Jann-Ella M. (Diliman, Quezon City College of Engineering, 2001)
D.Y. Manufacturing Corporation has been producing sheets and blown film for 23 years.Included in its plastic sheet product lines are the High Impact Polystyrene(HIPS), Acrylonitrite Butadine Styrene(ABS),and high and low density Polyenthylene.From these products,the plastic sheets compromise 80% of the company's total production.This is the reason behind the researchers focus on plastic sheets.By using failure mode effects analysis,the critical processes were determined and its corresponding failure mode,effect and cause were identified.Data from frequent plant visits,interviews and questionnaires aid in the process of identifying the quality problems experienced by the company.Through the Pereto analysis,the majo sources of defects were narrowed down to 4 problems.Furthermore,the Different Quality costs associated with these defects were considered resulting to the three quality problems in the study.These are specifically the variation in thickness,texture defects,and impact toughness.These three characteristics are now individually analyzed to pinpoint the different root causes and later generate recommendations to eliminate these.The ishikawa diagram was used to name the different root causes for individual problems.This was validated using the verification matrix that was formulated with the Plant manager and Quality Control Head.Design of experiments was also utilized n the course of making the study for identifying the factors affecting thickness.Through the DOE it was found that temperature directly affects thickness of the plastic sheets.Statistical process control was used to identify whether the process is in control or out of control.This is useful for predicting the performance of the processes After which,the process capability analysis was applied to know if it is producing within its pre-set standard and if this is met by the company.The company is producing plastic sheets with thickness that is out of control but can meet the specifications set.Temperature yielded an out of control process but is also capable.Texture is out of statistical control but capable at the same time.The variable impact toughness is in control but is incapable.An out of control process means that the process cannot be predicted in the failure and an in control process means that is predictable.A process that is capable implies that it is able to meet with the standards set by the company and a process that is not capably signifies that is not able meet the specifications.The company has its own inspection-sampling plan that it has been using from the beginning.This was also analyzed to determine if it is properly implemented and whether the right plan is being used.From this analysis,certain conclusions were drawn to aid the researchers in the generation of recommendations.It was concluded that the plan used for inspecting thickness, texture and impact toughness does not fir them and individual recommendations must be given.It is better to utilize the chain-sampling plan for thickness and impact toughness.It is also advisable to reduce the number of samples being inspected.After identifying the root causes conducting Statistical Process Control,Process capability,and Acceptance Sampling Analysis,different recommendations are generated that would address at least one these quality problems.Quality cost were also consider in generating the recommendations,after which the corresponding,implementation plan was designed.Recommendations include the training of operators and inspectors which would reduce the risk of errors thus reducing the cost,shifting operators to avoid human fatigue,improvement of maintenance to avoid the breakdown of machines,the documentation of standard operating procedures would serve as guidelines for the workers and the implementation of statistical process control would reduce the variability of the process and improve its predictability.This would dramatically improve the quality of D.Y.Manufacturing.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: D. Y. Manufacturing Corporation; Manufacturing industries; Quality control